Cranial osteology and neuroanatomy of the late Permian reptile Milleropsis pricei and implications for early reptile evolution - Xavier A. Jenkins; Roger B. J. Benson; David P. Ford; Claire Browning; Vincent Fernandez; Elizabeth Griffiths; Jonah Choiniere; Brandon R. Peecook (Royal Society Open Science)
Millerettidae are a group of superficially lizard-like Permian stem reptiles originally hypothesized as relevant to the ancestry of the reptile crown group, and particularly to lepidosaurs and archosaurs. Since the advent of cladistics, millerettids have typically been considered to be more distant relatives of crown reptiles as the earliest-diverging parareptiles and therefore outside of ‘Eureptilia’. Despite this cladistic consensus, some conspicuous features of millerettid anatomy invite reconsideration of their relationships. We provide a detailed description of the late Permian millerettid Milleropsis pricei using synchrotron X-ray phase-contrast micro-computed tomography focusing on the cranial anatomy of three individuals known from a burrow aggregation. Our data reveal a suite of neuroanatomical features Milleropsis shares with neodiapsids that are absent both in other ‘parareptiles’ and in early diverging groups of ‘eureptiles’. Traits shared between Milleropsis and neodiapsids include: the presence of a tympanic emargination on the quadrate, quadratojugal and squamosal, the loss of epipterygoid contribution to the basicranial articulation suggesting a more kinetic palatoquadrate, the absence of a sphenethmoid and the pathway of the abducens nerve through the braincase. Our findings suggest that the early reptile neurocranium, a region poorly sampled in phylogenetic analyses due to relative visual inaccessibility and poor preservation, has the potential to inform the phylogenetic relationships of early reptiles.